2009
DOI: 10.1016/j.trd.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the environmental benefits of ride-sharing: A case study of Dublin

Abstract: Ride-sharing has often been cited as a successful method to reduce congestion and green house gas emissions. This paper examines the patterns of ride-sharing, in Dublin, and estimates the environmental benefits of ride-sharing both in terms of reductions in emissions and the total vehicle kilometres travelled. Data from the 2006 Census of Ireland is used in this paper to examine the travel patterns of those that ride-share. Ride-sharing in Dublin currently accounts for 4% of the total morning peak commute trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(53 citation statements)
references
References 7 publications
0
53
0
Order By: Relevance
“…Jacobson and King investigated the potential fuel savings in the US when ride-sharing policy was announced and found that if 10% cars were to have more than one passenger, it could reduce 5.4% annual fuel consumption [29]. Caulfield estimated the environmental benefits of ride-sharing in Dublin and found that 12,674t of CO2 emissions were saved by individual ride-sharing [30]. Fellows and Pitfield examined the potential of ride-sharing to alleviate congestion and pollution and found evidence of its impact on reduction in vehicle kilometers, an increase in average speeds and savings in fuel, accidents and emissions [28].…”
Section: Traffic Congestion and Car Sharingmentioning
confidence: 99%
“…Jacobson and King investigated the potential fuel savings in the US when ride-sharing policy was announced and found that if 10% cars were to have more than one passenger, it could reduce 5.4% annual fuel consumption [29]. Caulfield estimated the environmental benefits of ride-sharing in Dublin and found that 12,674t of CO2 emissions were saved by individual ride-sharing [30]. Fellows and Pitfield examined the potential of ride-sharing to alleviate congestion and pollution and found evidence of its impact on reduction in vehicle kilometers, an increase in average speeds and savings in fuel, accidents and emissions [28].…”
Section: Traffic Congestion and Car Sharingmentioning
confidence: 99%
“…Scientific evidence on the benefits in terms of an absolute reduction of environmental pressure exists for personal ridesharing (e.g. Caulfield 2009). However, we are not aware of any scientific research on the sustainability impacts of a crowdsourced goods service based on real user data.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Ravenelle, 2017). Overall, carpooling is considered a sustainable form of transportation (Caulfield, 2009) and sustainability may be recognized as an asset of carpooling.…”
Section: Introductionmentioning
confidence: 99%